LAS CIENCIAS SOCIALES EN UN MUNDO GLOBALIZADO - Meschkat, Klaus (La Sociología en sus Escenarios, 2010)
Abstract. The presented document presented by the Dr. Klaus Meschkat in the University of Conception - Chile, is more a manifesto of political denunciation, on the occasion of an act of tribute to the professors, employees and students expelled from the Central Institute of Sociology of the same University, by military administration in the military coup of the 11 of September of 1973. Act of recognition that is realised 30 years later and that is concealed with the figure of the recognition to the contributions to social sciences of the mentioned professors. The dissertation of Professor Meschkat puts the real situation in the open that lived hundreds on professors, students and workers of that Chilean university and that has remained hidden by the local authorities. Resumen. Ponencia presentada por el Dr. Klaus Meschkat en la Universidad de Concepción Chile, con motivo de un acto de homenaje a los profesores, empleados y estudiantes expulsados del Instituto Central de Sociología de la misma Universidad, por la administración militar de la Universidad, encabezada por el rector Von Plessing, en el golpe militar del 11 de septiembre de 1973.Acto de reconocimiento que se realiza 30 años más tarde y que se encubre con la figura del reconocimiento a los aportes a las ciencias sociales de los profesores citados. La disertación del Profesor Meschkat pone al descubierto la real situación que vivieron cientos de profesores, estudiantes y trabajadores de esa universidad chilena y que ha permanecido oculta.